APLIKASI ASAM HUMIK DAN PUPUK NPK MAJEMUK TERHADAP PERTUMBUHAN TANAMAN SUREN (Toona sureni Merr) PADA TANAH MARGINAL - Marpaung, Ronald Pandapotan; Elfiati, Deni; D, Delvian (Peronema Forestry Science Journal, 2012)
The Marginal Land in Indonesia still in very large amount. Meanwhile, the accelerate to rehabilitate the land still very slow. The low of pH, C-Organik, N-Total, P and K-exchangeable become the parameter of marginal land condition. Therefore carried out research which combine acid humic and NPK fertilizer which applied to marginal land and seen its influence to growth of seed of suren. Research has been  done in green house at Faculty Of Agriculture of USU on March-May 2012 using completely randomized factorial design of two factors that is concentration of  humic acid ( 0%, 2.5% and 5%) and dose prular NPK fertilizer ( 0 gr; 1 gr; 2 gr; 3 gr and 4 gr per crop). The parameters observed were height of the plant, diameter of stem, dry wight, wide total of leaf and ratio of root crown. The results of research indicate that the concentration of humic acid do not have an effect on the reality to all of the parameters except to parameter of ratio of root crown. But dosage of  NPK fertilizer have significantly effect to all of the parameters. The combination of the concentration of humic acid and NPK fertilizer do not have an effect on the reality to all parameter. All of the dose of NPK fertilizer  besides control have a different significantly to the growth of the plant. Thereby, using of NPK fertilizer is good to growth of plant on marginal land media. Keyword : marginal land, humic acid, NPK fertilizer, seed of suren.